ANALISIS 3 DIMENSI GOOD GOVERNANCE DI KANTOR SAMSAT KABUPATEN SLEMAN - Raihan Hakam Naja; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Motor vehicle tax administration services at the Samsat Office of Sleman Regency represent a form of public service characterized by a high level of interaction between the government and the community. The identified issues relate to the clarity of service procedures, waiting time during service delivery, and the attitude of officers in serving the public. This study aims to analyze the implementation of the principles of transparency, effectiveness and efficiency, and accountability in public services at the Samsat Office of Sleman Regency, as well as to identify the supporting and inhibiting factors affecting their implementation. The research problems and objectives are examined using the concept of good governance through the principles of transparency, effectiveness and efficiency, and accountability as the analytical framework. This study employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation of service activities at the Samsat Office of Sleman Regency. The results indicate that the principles of transparency, effectiveness and efficiency, and accountability have been implemented through the provision of various service information channels, the application of a queue system, and mechanisms for supervision and public complaints. Service effectiveness is also supported by service innovations such as drive-thru services, mobile services, and the use of digital payment systems. The implementation of good governance principles has been carried out but has not yet reached an optimal level due to limitations in public digital literacy, fluctuations in the number of taxpayers, and the limited integration of digital service systems. This study recommends strengthening integrated digitalization of services and optimizing the drive-thru service innovation to improve the quality of public services at the Samsat Office of Sleman Regency.